Pengaruh Keterampilan Kerja, Kompensasi, dan Disiplin Kerja Terhadap Kinerja Karyawan - Alvinoav Pramudia Antatur; Qristin Violinda; Fadjar Darmaputra (Yayasan Al Ma'arif Dawuhan, 2024)
This study aims to examine the influence of job skills, compensation, and work discipline on employee performance, with PT. Misaja Mitra as the case study. A total of 253 respondents were selected through Probability Sampling to ensure representative data. Multiple Linear Regression Analysis was employed to analyze the data. The results reveal that the job skills variable (X1) does not have a significant impact on employee performance (Y), as indicated by a significance value of 0.181 (p > 0.05). In contrast, the compensation variable (X2) shows a positive and significant effect on employee performance (Y), with a significance value of 0.006 (p < 0.05). Similarly, the work discipline variable (X3) significantly and positively influences employee performance (Y), as demonstrated by a significance value of 0.000 (p < 0.05). These findings highlight the critical roles of compensation and work discipline in enhancing employee performance, while job skills appear to have a less direct impact. The study contributes to the body of knowledge in human resource management by emphasizing the need for organizations to focus on compensation strategies and fostering disciplined work environments to achieve optimal employee performance. However, further exploration is required to understand the underlying factors behind the insignificant relationship between job skills and employee performance. This research provides practical implications for PT. Misaja Mitra and similar organizations in designing effective human resource policies that prioritize compensation and work discipline as key drivers of performance enhancement.